In-situ TEM studies of ion-irradiation induced bubble development and mechanical deformation in model nuclear materials. Issue 1645 (2014) - Donnelly, S E; Greaves, G; Hinks, J A; Pawley, C J; Beaufort, M-F; Barbot, J-F; Oliviero, E; Webb, R P
ABSTRACT: The MIAMI* facility at the University of Huddersfield is one of a number of facilities worldwide that permit the ion irradiation of thin foils in-situ in a transmission electron microscope. MIAMI has been developed with a particular focus on enabling the in-situ implantation of helium and hydrogen into thin electron transparent foils, necessitating ion energies in the range 1 – 10 keV. In addition, however, ions of a variety of species can be provided at energies of up to 100 keV (for singly charged ions), enabling studies to focus on the build up of radiation damage in the absence or presence of implanted gas. This paper reports on a number of ongoing studies being carried out at MIAMI, and also at JANNuS (Orsay, France) and the IVEM / Ion Accelerator Facility (Argonne National Lab, US). This includes recent work on He bubbles in SiC and Cu; the former work concerned with modification to bubble populations by ion and electron beams and the latter project concerned with the formation of bubble super-lattices in metals. A study is also presented consisting of experiments aimed at shedding light on the origins of the dimensional changes known to occur in nuclear graphite under irradiation with either neutrons or ions. Single crystal graphite foils have been irradiated with 60 keV Xe ions in order to create a non-uniform damage profile throughout the foil thickness. This gives rise to varying basal-plane contraction throughout the foil resulting in almost macroscopic (micron scale) deformation of the graphite. These observations are presented and discussed with a view to reconciling them with current understanding of point defect behavior in graphite. *Microscope and Ion Accelerator for Materials Investigations